Ikhtiar al-Zaujah Limaskaniha: Dirasah fi al-Shariah al-Islamiyah Muqaranah bi tifaqiyah CEDAW al-Dauliyah - Afif Ateeli, Sajeda; Hj Abdullah, Raihanah (Jurnal Fiqh, 2015)
This research aims at elucidating the Islamic Sharia’s point of view concerning the woman’s right and freedom to choose her place of residence. The inquiry adopts a comparative method between two opposite perspectives, the Islamic Sharia and the Convention on the Elimination of all Forms of Discrimination against Women (CEDAW). The results illustrated in this research assert that in case of a dispute between spouses on their choice of residence, it is the husband’s right to decide and the wife is obliged to abide by his decision. This is a prerequisite for the implementation of the Islamic legal obligations and rights for each spouse to maintain the concept of family. Moreover, there will be no meaning of qawamah (guardianship) if spouses choose to live apart, and the wife will be deprived legal nafaqa (expense) if she leaves her husband’s house.